IRISIN AS A NOVEL DIAGNOSTIC BIOMARKER FOR INFLAMMATORY DISEASES: A REVIEW - Rana, Sadia; Abdul Wahab, Norsila; Wan Nazatul Shima Shahidan,; Atif, Saira; Fahim, Ayesha (Journal of Ayub Medical College Abbottabad, 2024)
Background: Inflammatory biomarkers are molecules that can offer vital information on the intricate chain of happenings and molecular processes underpinning the pathophysiology of any inflammatory disease. They can be measured in various biological samples such as blood, urine, or saliva, and are used as indicators of the presence and severity of inflammation. Measuring salivary inflammatory biomarkers is a non-invasive and relatively easy way to monitor inflammation, and it has been shown to be a useful tool in the diagnosis and management of various oral and systemic inflammatory diseases. Irisin is a novel anti-inflammatory protein and its implication and diagnostic role in inflammation have been widely studied; however, not much have been studied in oral inflammation per se. Irisin is predominantly downregulated in several inflammatory conditions, including obesity, type 2 diabetes, periodontitis, and cardiovascular diseases. This suggests that irisin may be involved in the inflammatory process, but more research is needed, especially of salivary irisin to understand its precise role. Overall, the role of irisin as an inflammatory biomarker is still an area of active research, and more studies are needed to determine its diagnostic and therapeutic potential. This review highlights the diagnostic and therapeutic potential of irisin in various systemic and oral inflammatory conditions.